1985
DOI: 10.1128/mcb.5.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Method of mapping DNA replication origins.

Abstract: We have developed a method which allows determination of the direction in which replication forks move through segments of chromosomal DNA for which cloned probes are available. The method is based on the facts that DNA restriction fragments containing replication forks migrate more slowly through agarose gels than do non-fork-containing fragments and that the extent of retardation of the fork-containing fragments is a function of the extent of replication. The procedure allows the identification of DNA replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…All of the DNA fragments in the 22 puM aphidicolin sample were equally faint, consistent with a low level of nonspecific DNA damage and repair that obscured any replication from ori. In addition, replication forks that remained in fragments G, I, and N would prevent normal migration of these DNA fragments during gel electrophoresis (4,26). These results were confirmed by extracting DNA from the early RI region of each gel as described below and then digesting it with a restriction endonuclease (data not shown).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…All of the DNA fragments in the 22 puM aphidicolin sample were equally faint, consistent with a low level of nonspecific DNA damage and repair that obscured any replication from ori. In addition, replication forks that remained in fragments G, I, and N would prevent normal migration of these DNA fragments during gel electrophoresis (4,26). These results were confirmed by extracting DNA from the early RI region of each gel as described below and then digesting it with a restriction endonuclease (data not shown).…”
mentioning
confidence: 77%
“…4. Replication forks must traverse the entire length of a restriction fragment for that fragment to be identified by gel electrophoresis, because restriction fragments containing replication forks migrate more slowly than those that are completely replicated, and the rate of migration varies with the number of forks and extent of replication (4,26). This complication means that the amount of a [32P]DNA fragment will be inversely proportional to its length as well as to its distance from the origin of DNA synthesis.…”
mentioning
confidence: 99%
“…Therefore, the total amount of form III 32P-labeled plasmid DNA observed was a measurement of total in vitro DNA synthesis (i.e., replication plus repair), while the amount of Dpn I resistant form III 32P-labeled plasmid DNA measured only DNA replication. When cut with EcoRI, replicating DNA intermediates (RI) produced molecules with branches of various lengths, depending on the extent of their replication, that migrated more slowly than form III DNA during gel electrophoresis and appeared as a smear of radioactivity (30,31;Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…We are grateful to Loretta Spotila for paving the way with her earlier work (10). We thank the following people for helpful discussions: Michael McCleland, Robert Benezra, Randall Morse, Les Davis, Robert Givens, Ravindra Hajela, and Jiguang Zhu.…”
Section: Acknowledgmentsmentioning
confidence: 95%
“…We have found that digestions shorter than 4 h at 37°C show no evidence of significant branch migration. For the experiments reported here, replicating SV40 DNA molecules were enriched by adsorption to BND-cellulose by a previously described column procedure (10). However, we have found that our recently described batch adsorption method (7) provides superior enrichment of replicating molecules (20-to 50-fold) with considerably less effort.…”
mentioning
confidence: 97%